Self-Acceptance in Breast Cancer Patients: A Concept Analysis - Putra Hadju, Febriyanto Dwi; Novany, Wafiq Aurelia; Masbait, Ermayanti; Karlistiyaningsih, Beta; Kasan, Nur; Pranata, Satriya (International Journal Labs, 2024)
Breast cancer is still one of the fears for most women in the world and ranks first regarding the number of cancers in Indonesia and is one of the first contributors to cancer deaths. Breast cancer patients with low self-acceptance will cause stress, lack of confidence, lack of enthusiasm for recovery and will affect poor health management. Self-acceptance is directly proportional to the patient's quality of life. The greater the patient's self-acceptance of their disease, the better the quality of life of breast cancer patients. The purpose of this analysis is to explain self-acceptance in breast cancer patients. An analysis of the concept of self-acceptance was conducted on articles published between 2019 and 2024. The databases used include Google Scholar, Proquest, Pubmed, and Science Direct. The results of the analysis show that the concept of self-acceptance has four attributes, namely, acceptance of physical changes, acceptance of physical and emotional limitations, accepting social and role limitations, accepting the healing process and uncertainty. Based on these attributes, nurses assess self-acceptance in breast cancer sufferers comprehensively. The results of the assessment will be the basis for nurses in determining appropriate diagnoses and nursing interventions to improve self-acceptance in breast cancer patients, by reducing psychological burden to improve quality of life.